Exploring the viability of a cognitive behavioural therapy-based activity for usage in a future anxiety intervention programme within the South African context - Webber, Louisa P. (Stellenbosch : Stellenbosch University, 2016)
ENGLISH ABSTRACT : Anxiety disorders constitute one of the most prevalent mental health problems in youth. High incidences of fear and anxiety symptoms have also been reported in research on South African children over the last decade; indicating a need for effective anxiety interventions specifically developed for South African children. However, there have been fewer studies to research the underpinning of cognitive behavioural therapy (CBT) based interventions for specific vulnerable children in the South African context. The study aimed to establish whether this proposed group of vulnerable South African children between the ages of 10 and 13 years possess the skills that are needed for engagement in CBT. The research objectives were twofold, firstly to explore whether a group of vulnerable South African children between the ages of 10 and 13 years could distinguish between thoughts, feelings and behaviours and secondly to determine if feedback during assessment improved performance. The participants consisted of a sample of 52 children between the ages of 10 and 13 years from a poverty-stricken neighbourhood in Stellenbosch, South Africa. A biographical questionnaire was completed by the researcher. The data collection commenced with the researcher asking the children to tell their favourite story. This created a child-friendly environment and was a good introduction to the CBT-based activity. The data collection was conducted in the child’s choice of language. As the researcher is not proficient in Xhosa, a translator was used. Taking into account cognitive developmental theory, cognitive behavioural theory as well as ecological systems theory, this activity was analysed quantitatively. Most of the participants could discriminate between thoughts, feelings and behaviours suggesting that they understand the core skills needed for participating in CBT. Conclusions will be drawn about the viability of this CBT-based activity for usage in a future anxiety intervention programme within the South African context.